1993
DOI: 10.1063/1.860582
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic instabilities in developed small-scale turbulence

Abstract: Modification of the magnetic force by a developed small-scale magnetohydrodynamic (MHD) turbulence can result in the sign reversal of the effective magnetic pressure. It is due to negative contribution of the MHD turbulence, to the large-scale magnetic force. It can significantly lower the elasticity of the large-scale magnetic field [ Sov. Phys. JETP 70, 878 (1990)]. This effect excites instabilities of the large-scale magnetic field due to the energy transfer from the turbulent pulsations to the latter. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 5 publications
0
54
0
Order By: Relevance
“…Direct numerical simulations (DNS) of Brandenburg et al (2011a) have shown in surprising detail many aspects of NEMPI that were previously seen in mean-field simulations (MFS) of Brandenburg et al (2010) and that have been anticipated based on analytical studies for some time (Kleeorin et al 1989(Kleeorin et al , 1990(Kleeorin et al , 1993(Kleeorin et al , 1996Kleeorin & Rogachevskii 1994;Rogachevskii & Kleeorin 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Direct numerical simulations (DNS) of Brandenburg et al (2011a) have shown in surprising detail many aspects of NEMPI that were previously seen in mean-field simulations (MFS) of Brandenburg et al (2010) and that have been anticipated based on analytical studies for some time (Kleeorin et al 1989(Kleeorin et al , 1990(Kleeorin et al , 1993(Kleeorin et al , 1996Kleeorin & Rogachevskii 1994;Rogachevskii & Kleeorin 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Using the spectral τ approach, Kleeorin et al (1989Kleeorin et al ( , 1990) do indeed find this reversal of the sign of the total magnetic tension force. In addition, they find a reversal of the sign of the effective magnetic pressure term; see also Kleeorin & Rogachevskii (1994) and Kleeorin et al (1993Kleeorin et al ( , 1996. Rogachevskii & Kleeorin (2007) argue that, in a stratified medium, this can lead to the formation of large-scale magnetic flux structures and perhaps even sunspots -or at least active regions.…”
Section: Introductionmentioning
confidence: 99%
“…This is quite the contrary of magnetic buoyancy, which is still expected to operate on the smaller scale of magnetic flux tubes and in the absence of turbulence. Both effects can lead to instability: the latter is the magnetic buoyancy or interchange instability (Newcomb 1961;Parker 1966), and the former is now often referred to as negative effective magnetic pressure instability (NEMPI), which has been studied at the level of mean-field theory for the past two decades (Kleeorin et al 1989(Kleeorin et al , 1990(Kleeorin et al , 1993(Kleeorin et al , 1996Kleeorin & Rogachevskii 1994;Rogachevskii & Kleeorin 2007). These are instabilities of a stratified continuous magnetic field, while the usual magnetic buoyancy instability requires nonuniform and initially separated horizontal magnetic flux tubes (Parker 1955;Spruit 1981;Schüssler et al 1994).…”
Section: Introductionmentioning
confidence: 99%